Multidrug-Resistant Tuberculosis during Pregnancy: Two Case Reports and Review of the Literature - Minakshi Rohilla; Bharti Joshi; Vanita Jain; Jasvinder Kalra; G. R. V. Prasad (Hindawi Limited, 2016)
Multidrug-resistant tuberculosis (MDR-TB) is identified from the time of introduction of antituberculosis treatment and is a known worldwide public health crisis affecting women of reproductive age group. Management issues raised by pregnant women with MDR tuberculosis are challenging due to the limited clinical experience available with the use of second line drugs. We hereby report two cases of MDR-TB during pregnancy: one patient was on second line drugs, while another one was evaluated and diagnosed to have MDR-TB in last trimester. At 6 months of follow-up both mothers and babies are doing well. The approach to such cases along with review of the literature is discussed.